Extended theory of planned behavior: a contextual framework for school mathematics reform - Prince Hamid Armah; Robert Benjamin Armah; Dennis Osei Yeboah; Matilda Sarpong Adusei (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study extends the theory of planned behavior (TPB) by testing a structural equation model that incorporates teachers perceived contextual support in explaining implementation of a problem-solving mathematics curriculum reform in Ghana. Using cross-sectional survey data from 368 primary teachers, we measured attitude, subjective norm, perceived behavioral control, intention, self-reported implementation behavior, and contextual support. Confirmatory factor analysis (CFA) supported the measurement model. Structural equation modelling (SEM) showed that attitude (β=.38, p<.001) and perceived behavioral control (β=.29, p<.001) predicted intention, while subjective norm was marginal (β=.12, p=.051). Intention predicted implementation behavior (β=.52, p<.001). Contextual support had a direct effect on behavior (β=.28, p<.001) and strengthened the intention to behavior relationship, which was larger in high support contexts (β=.63) than in low support contexts (β=.30; Δχ²(1)=7.84, p<.01). The model explained 57% of intention and 55% of behavior. Strengthening school resources, leadership support, and professional collaboration is likely to improve mathematics curriculum reform enactment. Policy makers and school leaders should prioritize these contextual supports to help teachers translate mathematics curriculum reform intentions into consistent practice.